Innovation of Hajj and Umrah Worship Services in The Pandemic Time in Indonesia (in Sharia Insurance Perspective) - Reza Ronaldo; Yul Maulini (Sekolah Tinggi Ekonomi dan Bisnis Islam Lampung, 2021)
This study aims to innovate the implementation of the Hajj and Umrah pilgrimages in order to improve the welfare of the guests of Allah SWT who fulfill the fifth pillar of Islam as well as to improve the image of the Government of the Republic of Indonesia, which has the largest Muslim community in the world. The research method used is a qualitative method with data support. The analytical technique is used to explain the findings by observing and conducting an inventory of previous studies related to the Organization of the Hajj and Umrah. This finding shows that in general the implementation of the Hajj and Umrah in Indonesia still needs to be improved, especially from the insurance aspect. Innovation in the Sharia insurance sector can be done through bundling life insurance products and general insurance, with a compensation value and greater for pilgrims who have died as well as providing compensation to the heirs of the congregation who have experienced a disaster as well as additional insurance coverage for pilgrims affected by Covid-19. The extent of insurance coverage can be innovated by increasing the value of the guarantee for the goods/baggage of the congregants who lost as well as an increase in the value of hospitalization guarantees in hospitals for pilgrims who experience accidents, heart attacks, and others. Sharia insurance is the main choice according to the fatwa of the National Sharia Council (DSN) to provide protection as well as innovation. With better service for the congregation, the level of satisfaction of the congregation with the government will increase.